Influence of Heparin and Seminal Heparin Binding Proteins on Reproductive Performance of Sahiwalfriesian Bulls and Rabbits - Patchaiappan, Ramakrishnan (2003)
A study was undertaken to characterise seminal heparin binding proteins (HBP) of Sahiwal-Friesian bulls and rabbits and to investigate the influence of HBP on the reproductive performance of Sahiwal-Friesian bulls and rabbits. Using one dimensional sodium dodecyl sulfate-polyacrylamide (SDS-PAGE) gel electrophoresis, the major classes of HBP identified and isolated from Sahiwal-Friesian bulls and rabbits were with molecular weights of 15, 25, 30, 38 and 42, 15, 25, 38, 42 and 101 kDa, respectively. Bulls of varying fertility were found to have similar classes of HBP in their seminal fluids in the present study. This may show that the presence of the different classes of HBP in seminal fluid may not be an indicative of bull fertility. Heparin and lyophilised HBP were found to have no effect on the percentage of spermatozoa motility in Sahiwal-Friesian buIIs and rabbits. However, the addition of heparin or Iyophilised HBP to epididymal spermatozoa and ejaculated spermatozoa has significantly increased the rate of acrosome reaction in both the species. The present study also showed that rabbits inseminated with epididymal spermatozoa without the addition of HBP produced significantly higher mean Jittered rates and mean litter born per doe as compared to those animals inseminated with epididymal spermatozoa treated with d ifferent levels of HBP. These results showed that epididymal spermatozoa of rabbit could fertilise oocytes without prior exposure to HBP or seminal fluid whose HBP were believed to be necessary for capacitation of spermatozoa in cattle and rabbit. The group of rabbits inseminated with epididymal spermatozoa treated with HBP at the rate of 4 mg/ml, recorded significantly lower mean litter born per doe as compared to those female rabbits inseminated with epididymal spermatozoa treated with HBP at the lower rates. These results may show that a higher concentration of lyophilized HBP causes more damage to the epididymal spermatozoa instead of further improving their fertilising ability. Among the four groups of rabbits inseminated with epididymal spermatozoa (ES), epididymal spennatozoa with HBP (ESII), ejaculated spennatozoa (ESM) and ejaculated spennatozoa with HBP (ESMH), there was no significant difference found for the litter rate between the groups inseminated at 0 hour. However, for animals inseminated at 6 hours after induction of ovulation, the litter rate was significantly lower in the group inseminated with ES as compared to the other three groups which were inseminated with spennatozoa which had either natural HBP or added lyophilised HBP. In the present study, it was also found that none of the female rabbits inseminated at 12 and 24 hours after the vaginal stimulation littered. It was also observed that epididymal spennatozoa samples added with Iyophilised HBP bound significantly higher concentration of tritiated (3H) heparin to their membrane as compared to samples that were devoid of HBP. The present study also showed that higher fertile bulls bound significantly higher concentrations of (3H) heparin to their spennatozoa membrane than the lower fertile bulls. From this study, it can be concluded that (i) epididymal spennatozoa of rabbits could fertilise oocytes without prior exposure to HBP or seminal fluid in the rabbit and (ii) Sahiwal-Friesian bulls could be selected based on their ability to hind (3H) heparin to their spemmtozoa.